(untitled) (LACCEI, 2024)
The international call to highlight the problems related to women’s equal rights and opportunities is growing. One of these problems is the minority participation of women in engineering programs, which is due to multiple factors and is evident both in access, permanence and graduation. This negatively impacts society with the loss of women’s talents to build a sustainable world, an issue that is closely related to the sustainable development agenda of the United Nations Organization, through two of its objectives: SDG 5, to achieve Gender Equality, and SDG 4, Quality Education, to which the Faculties of Engineering adhere. It is propitious that, among the generic competences for engineering training in Latin America, which were proposed by CONFEDI in 2006 and assumed by ASIBEI in 2014, are the so-called Social, Political and Attitudinal. Also noteworthy is the joint recognition made by ACOFI, LACCEI and CONFEDI to the existence of the gender gap in the field of Engineering, through the creation of the Matilda Latin American Open Chair and Women Engineers, in 2020, and Commissions that address the theme in their own contexts. Quality education in Engineering finds an opportunity to consolidate strengths and address weaknesses, especially in instances of change of study plans and in the proximity of accreditation processes for the Argentine context, the gender gap being a challenge to consider. In line, and with the idea of contributing to these processes of transformation and innovation, a proposal is presented for the integration of the gender vision as part of the formation of social, political and attitudinal competences in engineering programs.